HUBUNGAN POLIMORFISME GEN RESEPTOR ESTROGEN ALFA DENGAN JUMLAH SEL T CD4+ PADA ANAK TERINFEKSI HIV - Irna Sufiawati; Risti Saptarini; Eriska Riyanti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2017)
Background: Estrogen plays a key role in human physiological processes. Polymorphisms of estrogen receptors have been implicated in the development of numerous diseases. The aim of this study was to evaluate the frequency of ERα gene Pvull and Xbal polymorphisms and assessing their association with CD4+ T-cell counts in HIV-infected children on highly active antiretroviral therapy.Methods: CD4+ T cell counts were determined using the FACS count system. ERα PvuII and XbaI polymorphisms were analyzed by PCR-RFLP.Results: This study enrolled 34 HIV-infected children on HAART. The frequencies of the PvuII and XbaI gene polymorphisms were PP 41,2%, Pp 26,5%, pp 32,4% and XX 35,3%, Xx 17,6%, xx 47,1% respectively. CD4+ T-cell counts were significantly associated with XbaI polymorphisms (p<0.05), but not PvuII polymorphisms (p>0.01).Discussion: Host genetic factor polymorphism is an important determinant of HIV disease progression and treatment response. The ERα Pvull and Xbal polymorphisms can increase risk for the development of HIV-related complication,including oral diseases.Conclusion: The ERα gene XbaI polymorphism was significantly associated with CD4+ T-cell counts. It may explain the role of estrogen in the regulation of HIV replication. Studying human genetic variation in HIV-infected individuals is important to guide a new therapeutic approach.